Factorial design methodology to determine optimum speed of an internal combustion engine for a generator - Agrawal A.K.; Sinqh R.S.; Chaudhary P.K. (My University, 2025)
With the shortage in electricity supply in many parts of India, dependency is increasing heavily upon the usage of generators for meeting out the power requirement. The generators are generally coupled with internal combustion engines of either type: petrol or diesel. In practice, the generators are run from practically no load to full load condition but at a fixed rpm. Thus, the engines are supposed to generate varying amount of power at a constant speed. It has been found that the fuel consumption varies with the ambient condition, engine speed and power requirement. In this paper, an approach has been suggested, that can be used to determine the optimal speed at which if the engine runs, then on an average the fuel consumption would be the least for varying levels of ambient condition and power requirement.